Test of resistance in some of rice varieties to pathogenic bacteria Burkholderia Glumae. Issue 1 (April 2020) - Amirullah, Jazman Chaerul; Baharuddin,; Kuswinanti, Tutik
Abstract: Burkholderia glumae is a bacterium that causes grain rot disease in rice plants. In Indonesia, the disease inflicts yield losses to farmers but there have been no clear reports of the level of the attacks. This study was aimed to determine the development of the grain rot symptoms and the resistance of several rice varieties to grain rot disease. Eleven rice varieties that had been widely used by the farmers in South Sulawesi Province tested in this experiment. The B. glumae isolate used came from previous studies in our laboratory. B. glumae inoculation was performed in the generative phases of the rice plants by spraying the flowering panicles. Observations in the form of the impact of B. glumae inoculation on symptom incubation, and resistance of the varieties against the rice grains disease. In the generative phase, typical symptoms of grain rot disease developed on the inoculated plants. The varieties reaction against the disease varied. Varieties of Inpari 30, Inpari 4, Cigeulis, Ciliwung, Ciherang, and Inpari were highly resistant; Mekongga, Inpari 32 and Sidenuk varieties were medium to strong, then Inpari 33 was medium. Then the Cisantana variety was low to moderate. Of the eleven varieties, Cisantana variety has the highest severity of 61.02% and variety resistance is weak to medium. Further testing in the laboratory is needed to determine the presence of B. glumae which has been inoculated into plant tissue by sampling symptomatic and asymptomatic rice plants.